Dash - Larson, Kirby (Scholastic Press, 2014)
When her family is forced into an internment camp, Mitsi Kashino is separated from her home, her classmates, and her beloved dog Dash; and as her family begins to come apart around her, Mitsi clings to her one connection to the outer world...the letters from the kindly neighbor who is caring for Dash